Hydrodynamic controls of morpho-sedimentary evolution in a rock-bounded mesotidal estuary. Tina Menor (N Spain) - Flor-Blanco, G.; Flor, G.; Morales, J. A.; Pando, L. (Journal of Iberian Geology, 2015)
The Tina Menor estuary is a highly confined incised valley with advanced sedimentary infilling. The outstanding feature of this estuary is its longitudinal zonation, which forms four segments from the outer to the inner limit: Mouth complex, Bay, Tidal flats and Upper channel. The innermost part of the Bay and the Tidal Flats (semi-reclaimed areas) are broader estuarine zones, whereas the Mouth Complex and outermost Bay are confined by narrow rocky outcrops. This paper explains the dynamics and sedimentary distribution of a highly confined and singular estuary, detailing the fluvial-tidal controls on the variations in water mixing (QF/QT). This estuary is largely of salt wedge type and the dynamics are characterised by recording currents (speed and direction) in the water column during a tidal cycle in a spring tide; this process consists of the tidal waves propagation and their dissipation upstream hypo-synchronously and the mixing of fresh and saline waters. The morphology, dynamics and sedimentary distributions have been integrated to develop a conceptual model that demonstrates the circulation within the estuary. The sinuous geometry of the estuarine valley and the Coriolis Effect detected, play a fundamental role in determining the morphology and sedimentary distribution. Consequently, this study provides an adequate overview of this type of confined mesotidal estuary, quite common in the eastern Atlantic coast. The mrophology, dynamics and sedimentary distributions have been integrated to develop a conceptual model that demonstrates the circulation within the estuary. The sinous geometry of the estuarine valley and the Coriolis effect detected, play a fundamental role in determining the morphology and sedimentary distribution. Consequently, this study provides an adequate overview of this type of confined mesotidal estuary, quite common in the eastern Atlantic coast.